Executive Committee Minutes 2011-04-28 - Academic Senate:::::::::
Chair Report. Agenda amended and approved. Minutes of 4/7/11 approved. CFA Report. Chair-Elect Report. Provost Report. Statewide Senator Report. Vice President of Administration and Finance Report. Vice President of SAEM Report. From the Curriculum Guide: Discontinuance Policy approved for Senate agenda. Economics revisions approved for Senate consent calendar. Chemistry revisions approved for Senate consent calendar. Engineering revisions approved for Senate consent calendar. Executive MBA revisions approved as a business item. Motion concerning recent Student Fee Referendum approved for Senate agenda. Senate agenda approved.